2014
DOI: 10.1074/jbc.m113.520403
|View full text |Cite
|
Sign up to set email alerts
|

A Redox-resistant Sirtuin-1 Mutant Protects against Hepatic Metabolic and Oxidant Stress

Abstract: Background: Sirtuin-1 improves metabolic disease, but oxidants may inhibit it. Results: Metabolic stress increased glutathione adducts, inactivated endogenous Sirtuin-1, and promoted apoptosis. A novel Sirtuin-1 oxidation-insensitive mutant or glutaredoxin-1 prevented metabolic dysregulation and apoptosis. Conclusion: A novel Sirtuin-1 mutant circumvents oxidation and more effectively inhibits metabolic dysregulation and apoptosis. Significance: Oxidative inactivation of Sirtuin-1 contributes to metabolic dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 71 publications
(85 reference statements)
5
73
0
Order By: Relevance
“…We have previously shown that metabolic or nitrosative stress increases SirT1 reversible oxidative modification, which inhibits its enzyme activity and promotes hepatocyte apoptosis (67). Consistent with these findings, here we demonstrated that Glrx deficiency decreases SirT1 activity by GSH adducts and consequently increases acetylation of Srebp1 and expression of lipid synthesis genes, including Fasn and Scd1 in the liver (Fig.…”
Section: Glrxsupporting
confidence: 79%
See 4 more Smart Citations
“…We have previously shown that metabolic or nitrosative stress increases SirT1 reversible oxidative modification, which inhibits its enzyme activity and promotes hepatocyte apoptosis (67). Consistent with these findings, here we demonstrated that Glrx deficiency decreases SirT1 activity by GSH adducts and consequently increases acetylation of Srebp1 and expression of lipid synthesis genes, including Fasn and Scd1 in the liver (Fig.…”
Section: Glrxsupporting
confidence: 79%
“…Activation of SirT1 improved NAFL and conversely hepatic SirT1 deficiency led to steatosis (56). Inhibition of SirT1 activity by reversible GSH adducts has recently been described by our group and was confirmed by other investigators (11,67,71,77). Because NAFL (58) is associated with oxidative stress, increased protein GSH adducts may play an important role in the pathogenesis of steatotic livers.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations